Expression of Eukaryotic Translation Initiation Factors in the Urothelial Carcinoma of the Bladder - Luzha, Jeton; Nass, Norbert; Czapiewski, Piotr; Schroeder, Nicolas; Kalinski, Thomas; Schostak, Martin; Schatz, Christoph; Jandrig, Burkhard; Haybaeck, Johannes (Anticancer Research, 2023)
BACKGROUND/AIM: Urothelial carcinoma (UC) of the urinary bladder is the second most common tumor in the field of urology and is characterized by a relatively aggressive growth behavior. New therapeutic approaches are required to improve the prognosis of affected patients. We hypothesized a link between dysregulation of eIFs and the development of UC. Therefore, in the present work, we investigated the expression behavior of eIF1, eIF1AY, eIF1AX, eIF2α, eIF3a, eIF3b, eIF4B, eIF4E, eIF4G, eIF5A, eIF5B, and eIF6 in UC compared with that in urothelial tissue. MATERIALS AND METHODS: Paraffin-embedded tumor tissue samples from 107 patients suffering from UC were examined. Seventy-six patients contained adjacent urothelial tissue. Three tumor tissue cylinders (tumor collective) and two urothelial tissue cylinders (control collective) were collected per patient and embedded in tissue microarray (TMA) blocks. Immunohistochemical staining of the TMA sections was then performed. The staining results were assessed semi-quantitatively. Staining intensities and immunoreactive scores (IRS) of both collectives were compared. In each case, a distinction was made between cytoplasmic and nuclear staining. RESULTS: Significant up-regulation of eIF1AY, eIF2α, eIF3a, eIF3b, eIF4B, eIF4G, eIF5B, and eIF6 was found in the cytoplasm of UC. In contrast, eIF1 and eIF5A were significantly down-regulated in the cytoplasm of UC. eIF5A and eIF6 were significantly down-regulated in the nuclei of UC. CONCLUSION: Dysregulation of eIFs in the urothelium of the urinary bladder is linked to carcinogenesis at this site.
CRIS-Team Scopus Importer:2023-04-07
Keywords: bladder cancer; eukaryotic initiation factors (eIFs); initiation; Translation; urothelial carcinoma